Effect of Reinforcement Volume Ratio on Thermal Conductivity of SiO2 Reinforced Al Matrix Composite Produced by Vacuum Infiltration Method - CALIN, RECEP (Asian Journal of Chemistry, 2009)
In this study, SiO2 powders with 105 μm particle size were filled inquartz tubes freely to form 30, 40, 50 % reinforcement volume ratios.Liquid Al7075 alloy was vacuum infiltrated into the SiO2 compact underthe same vacuum condition, the same time and at the same temperaturein normal atmosphere for 3 min. After vacuuming, infiltration heightand density of product composite have been determined. Microstructuresof composites were investigated by SEM analysis. Two methods, finiteelement analysis method and experimental method, were used to determinethermal conductivity. The results of these methods were evaluatedand compared. It has been found that the values of two different methodswere quite near each other and thermal conductivity of composite increasedwith decreasing reinforcement volume ratio.